Dislexia e TDA/H no ensino superior: o recurso à medicalização como privilégio para o ingresso? - Rodrigues, Thais de Sousa (2018)
Medicalization refers to the process of pathologization of daily situations there are approached by a medical and biologic point of view and underpinned by an individualized way. From a nosological perspective and related to learned process, we find purported disorders as Dyslexia and Attention Deficit /Hyperactivity Disorder (ADHD) in different education levels. In this regard, this research has as general objective to know and to analyse Dyslexia and ADHD technical reports used for entry to Higher Education through Cultural-historical Theory contributions and, as specific objective, to propose School Pshicology on medicalization confronting on Higher Education. On this study, with quality focus, we proceeded to a technical reports survey between 2003 and 2016 showed for candidates to responsible sector by Federal University of Uberlândia (UFU) selective processes; we realized semi-structure interview with employee responsible for exceptional care sector, we did phone contact to Teaching, Research and Extension Center Assistance in Special Education (CEPAE) and we did an observation during the test application of the special sector, monitoring candidates who entered with Dyslexia and ADHD requests and technical reports, as visual, hearing, physical impairment and another necessities. On survey we found 809 requests, 96 candidates with Dyslexia and ADHD, 42 females and 54 males, 34 candidates with intention to Medical course. The number request increased between 2003 and 2016, just as pills used, since 32 candidates use methylphenidate. Through a careful reading of requests and technical reports, the interview transcription and the field diary, we choose five axes to analyse: 1) Medical supremacy: the “doctor” status; 2) School or drugstore? It hurts a lot to do entrance examination? 3) The symptoms appropriation and the collateral effects naturalisation; 4) Disability, disorder, dysfunction or “story to sleeping ox”? After all, what are ADHD and Dyslexia? and 5) If ADHD and Dyslexia are not disabilities, why there are included in exceptional care service?. Therefore, we propose to create an internal committee in UFU, composed of multidisciplinary staff, with psychologists participation to evaluate these exceptional care requests and to act on diagnostic deconstruction. Besides that, we purpose that some of these resources that are offered to exceptional care candidates, such as the time extension test up to one hour, there are expanded to all candidates, without the necessity of a technical report that attests some purported disorder. We believe that the care exceptional service offered to people with Dyslexia and ADHD contributes just not to the technical supports proliferation, as such to use of medicines, that contributes to increased of life medicalization. Thus, we believe that this study comes to contribute just not to alert, but to report medicalization practice, that are happening in a lot of contexts, as the Higher Education. We defend a Higher Education that can be access to any students that are interested to continue their studies in this level of teaching and that, in their past schooling, they are respected and assisted in their different kind and time of learning and they were not induced to believe or make use purported disorders, such as Dyslexia and ADHD, as a benefit to entry on college.